Aplicación de técnicas electroanalísticas en la determinación de plomo en agua potable. - Gonzalez Zhiñin, Andrea Esthefania (2015)
The objective of this research is the identification and quantification of heavy metal Pb, it could be given the lead content in drinking tap water, especially if your home has plumbing materials such as solder or lead pipes, is surely there is presence of lead. As the main methodology for our research we have used the application of electroanalytical techniques called anodic stripping voltammetry.